Approximation and Online Algorithms 6th International Workshop, WAOA 2008, Karlsruhe, Germany, September 18-19, 2008, Revised Papers - Bampis, Evripidis; Skutella, Martin (Theoretical Computer Science and General Issues,, 2009)
This book constitutes the thoroughly refereed post workshop proceedings of the 6th International Workshop on Approximation and Online Algorithms, WAOA 2008, held in Karlsruhe, Germany, in September 2008 as part of the ALGO 2008 conference event. The 22 revised full papers presented were carefully reviewed and selected from 56 submissions. The workshop covered areas such as algorithmic game theory, approximation classes, coloring and partitioning, competitive analysis, computational finance, cuts and connectivity, geometric problems, inapproximability results, mechanism design, network design, packing and covering, paradigms for design and analysis of approximation and online algorithms, randomization techniques, real-world applications, and scheduling problems.